(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
The article investigates the phenotypic plasticity of common bream (Abramis brama) in the lower reaches of the Zarafshan River under conditions of anthropogenic and environmental transformation. The study reveals the impact of changes in the hydrological regime, water mineralization levels, and the food base on body morphometry. The results clarify the adaptation mechanisms of the species to extreme conditions.